Update New Water Technology Headed for Parched Places. - Adee, S.
This article deals with a project to build experimental water-purification reactors in drought-plagued northeastern Australia. Parched cities in Queensland and New South Wales are turning to capacitive deionization (CDI), an electric field-based seawater desalination technology that could make inland water desalination much more affordable.
Keywords: New South Wales; Queensland; Capacitive deionization; Drought-plagued northeastern Australia; Electric field-based seawater desalination; Parched city; Water-purification reactors